Encounters of the brahmanical Sanskrit tradition with Persian scholarship in the Mughal Empire: genealogical critique and the relevance of the pre-colonial past in a global religious history - Bergunder, Michael (Interdisciplinary journal for religion and transformation in contemporary society, 2024)
Within the scope of global religious history, a Foucauldian genealogical critique makes “history” itself the central focus of inquiry. Genealogy is usually perceived as a methodology for historicizing general concepts within religious studies, which seemingly favours post-nineteenth-century history – something that causes discomfort among pre-colonial researchers. However, this article presents genealogy as a general starting point for any critical historiography across all historical periods, emphasizing its key characteristic as a counter-history originating from the present.
Online veröffentlicht: 30. Januar 2024